Insights from Imaging in Bioinorganic Chemistry - Eldik, Rudi van; Hubbard, Colin D.; ScienceDirect eBooks (Cambridge, MA : Academic Press, 2016)
Annotation This volume continues a long-running series that describes recent advances in scientific research, in particular, in the field of inorganic chemistry. Several highly regarded experts, mostly from academe, contribute on specific topics.
Text in English.
Online resource; title from PDF title page (EBSCO, viewed January 14, 2016)
Includes bibliographical references and index.
Elsevier
Keywords: Bioinorganic chemistry; Imaging systems in chemistry; SCIENCE / Life Sciences / Biochemistry; Bioinorganic chemistry; Imaging systems in chemistry; Electronic books